2022
DOI: 10.3390/su141710843
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Units Optimization in Pneumatic Spray Delivery-Based Fixed Spray System for Large-Scale Commercial Adaptation

Abstract: A pneumatic spray delivery (PSD)-based solid set canopy delivery system (SSCDS) consists of in-line reservoirs and micro-emitter assemblies distributed throughout perennial crop canopies. The existing PSD-based SSCDS uses a large number of reservoirs, i.e., one unit per 3 m of linear spacing, which resulted in high installation and maintenance costs. These reservoirs also produces up to 25% post-spray chemical losses. Therefore, this study aimed to optimize the volumetric capacity and functionality of the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to characteristics of the citrus canopy structure during the autumn shooting period and their requirements for plant protection, the canopy was divided into three dimensions for sampling, including the horizontal direction, vertical direction, and circumferential direction [23,24].…”
Section: Sampling Point Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to characteristics of the citrus canopy structure during the autumn shooting period and their requirements for plant protection, the canopy was divided into three dimensions for sampling, including the horizontal direction, vertical direction, and circumferential direction [23,24].…”
Section: Sampling Point Arrangementsmentioning
confidence: 99%
“…Mozzanini et al [22] evaluated the suitability of a hydraulic fixed delivery spray system to be adopted as crop protection technology and found that the emitter flow rate, emitter number, and spray mixture volume injected were the three key factors affecting the dose applied, homogeneity of distribution among emitters, and cleaning performance. Sahni et al [23] investigated the spray effect of a pneumatic spray delivery-based solid set canopy delivery system in a high-density apple orchard, and the results showed that modified reservoirs and a three-tier configuration offered significantly improved zonal coverage uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has extensively researched SSCDS configurations for tall spindle apple architectures typical in WA state. 38,[40][41][42][43][44] PSDbased SSCDS developed by Sinha et al provided improved spray deposition and uniform spray discharge along the spray line compared with hydraulic-based SSCDS 38 . Our latest optimal PSDbased SSCDS provided similar spray deposition, reduced ground drift and negligible aerial drift, but lower spray coverage compared with an airblast sprayer in tall spindle apple orchard.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has extensively researched SSCDS configurations for tall spindle apple architectures typical in WA state 38,40–44 . PSD‐based SSCDS developed by Sinha et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation